E-165 Woven endobridge versus stent-assisted coil embolization of cerebral bifurcation aneurysms. (23rd July 2022) - El Naamani, K; Chen, C; Abbas, R; Sweid, A; Sioutas, G; Ramesh, S; Tjoumakaris, S; Gooch, M; Herial, N; Zarzour, H; Schmidt, R; Rosenwasser, R; et al.
Abstract : Background: Stent-assisted coil (SAC) embolization has been the mainstay endovascular treatment for bifurcation aneurysms. Recent introduction of the Woven EndoBridge (WEB) device has presented an alternative endovascular treatment modality for these aneurysms. Direct comparison of outcomes between the two modalities in the literature are limited. Objective: To compare the outcomes of bifurcation aneurysms treated using SAC and WEB. Methods: This is a retrospective, single-center study, comprising 148 bifurcation aneurysms treated endovascularly using SAC or WEB devices between 2011 and 2019. The primary outcome was complete occlusion of the aneurysm at 6 months based on catheter angiography. Results: The SAC and WEB cohorts comprised 85 and 63 aneurysms, respectively. The baseline characteristics were well balanced after IPW adjustment except for smoking status. The 6-month complete occlusion rate was higher in the WEB vs. SAC cohort (67.4% vs. 40.6%; unadjusted OR=3.014 [1.385–6.563], p=0.005). However, this difference in complete occlusion rates did not remain significant after inverse probability weights (IPW) adjustment and multiple imputations. Neck remnant rate was lower in the WEB vs. SAC cohort (20% vs. 50%; OR=0.250 [0.107–0.584], p=0.001), and this remained significant after IPW adjustment (aOR=0.296 [0.096–0.915], p=0.035) and multiple imputations (aOR=0.307 [0.114–0.826], p=0.019). Rates of other secondary outcomes were comparable between the two cohorts in unadjusted and adjusted analyses. Conclusion: SAC and WEB demonstrated comparable 6-month complete occlusion rates for bifurcation aneurysms. WEB appeared to be associated with a lower rate of neck remnant compared to SAC. WEB was also associated with fewer complications compared to SAC. Disclosures: K. El Naamani: None. C. Chen: None. R. Abbas: None. A. Sweid: None. G. Sioutas: None. S. Ramesh: None. S. Tjoumakaris: 2; C; Medtronic, Microvention. M. Gooch: 2; C; Stryker. N. Herial: None. H. Zarzour: None. R. Schmidt: None. R. Rosenwasser: None. P. Jabbour: 2; C; Medtronic, Microvention, Balt, Cerus Endovascular.